Processo de compra de produtos para recém-nascidos na feira hippie de Goiânia-GO: um olhar antropológico - Cardoso Sobrinho, Carlos Antonio (2012)
The theme of this dissertation addresses one aspect of the business anthropology that is Anthropology of Consumption. The growing interest in the subject, both within academic and marketing, has instigated the development of this research. The fact that has contributed to the increase of production on the issue discussed, is the proximity between marketing, consumer behavior and anthropological view. The search for understanding consumer behavior through the prism interpretive grounded in qualitative methods of data collection, rather than a quantitative approach, the anthropology of consumption is an issue capable of working with cultural and symbolic aspects that involve the act to consume. In this context, it was established as a goal, interpret the symbolic manifestations identified during the process of formation of newborn layette. The object of analysis it is a periodic market, chosen by the ethnic plurality and behavior of users of the site. The theoretical concepts from the business covered anthropology, through interdisciplinary discussion involving the social sciences and applied social sciences and reaching the creation and evolution of the anthropology of consumption, deepening further the use of ethnography in market scenarios. To achieve the methodological purpose of the dissertation, ethnography as a procedure for implementing the field work. This method was suitable for the commercial context, therefore, through the quasi-ethnography, there was a non-participant observation, and data were recorded in a diary and later analyzed. The information resulted in three areas of analysis of the factors that influence consumer behavior: a) the dynamics of the fair; b) the aisle stories, c) the role of individuals in the process. The results show the influence of environment on consumer relationship and interactionbetween individuals, explaining how relevant are the symbolic meanings for the formation of the act of consuming. As to the conduct of ethnographic work, reinforced the premise of the method has potential to involve observed and noted, providing a view of the phenomenon without intermediaries with data collected directly from the source.